2020
DOI: 10.1099/mgen.0.000444
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and mitochondrial genome sequencing of North-African Leishmania infantum isolates from cured and relapsed visceral leishmaniasis patients reveals variations correlating with geography and phenotype

Abstract: Although several studies have investigated genetic diversity of Leishmania infantum in North Africa, genome-wide analyses are lacking. Here, we conducted comparative analyses of nuclear and mitochondrial genomes of seven L. infantum isolates from Tunisia with the aim to gain insight into factors that drive genomic and phenotypic adaptation. Isolates were from cured (n=4) and recurrent (n=3) visceral leishmaniasis (VL) cases, originating from northern (n=2) and central (n=5) Tunisia, where respectively stable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 59 publications
5
15
0
Order By: Relevance
“…Previously, various studies have described aneuploidy as an important mechanism of adaptation used by Old and New World Leishmania species [36, 40, 41, 65, 66]; however, few studies have focused on analysing whether the structural changes observed in species are maintained across different geographical regions. The results obtained confirm not only the widely described [10, 12–15, 41, 65, 67] extensive aneuploidy of L. infantum but also the conservation of these structural changes at the global level ( and S2), which suggests that, regardless of the genetic background of the host and the eco-epidemiological niche in which the parasite exists, the chromosomal architecture of L. infantum needed to undergo extensive changes during possible adaptation mechanisms. On the other hand, and despite observing a low number of genes with CNVs in our dataset (), the ontology enrichment analysis revealed an increase, at the global level, in genes directly involved with the virulence and infectivity of the parasite (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previously, various studies have described aneuploidy as an important mechanism of adaptation used by Old and New World Leishmania species [36, 40, 41, 65, 66]; however, few studies have focused on analysing whether the structural changes observed in species are maintained across different geographical regions. The results obtained confirm not only the widely described [10, 12–15, 41, 65, 67] extensive aneuploidy of L. infantum but also the conservation of these structural changes at the global level ( and S2), which suggests that, regardless of the genetic background of the host and the eco-epidemiological niche in which the parasite exists, the chromosomal architecture of L. infantum needed to undergo extensive changes during possible adaptation mechanisms. On the other hand, and despite observing a low number of genes with CNVs in our dataset (), the ontology enrichment analysis revealed an increase, at the global level, in genes directly involved with the virulence and infectivity of the parasite (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Since 2007, when the whole genome of L. infantum was sequenced and published for the first time, various studies using DNA-sequencing technology revealed important findings for this species. Those research efforts facilitated an understanding of its genetic structure [8]; the analysis of the genomic variations associated with the clinical features, hosts and treatment responses [9,10]; the identification of markers of drug resistance [11]; the determination of the genomic diversity in geographically restricted regions [9,10,12,13] and globally [14]; as well as the low OPEN ACCESS plasticity and intra-specific genomic variability that characterize this Leishmania species [10,14,15]. To date, these studies have focused mainly in specific geographical areas, such as Brazil, leaving the genomic diversity of this species in other regions of the world unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the type of exploratory data analyses and the biological questions that can be addressed, we tested giptools on a previously analyzed dataset of seven clinical Leishmania infantum isolates from Tunisia (14). Leishmania is the etiological agent of leishmaniasis, a life-threatening human and veterinary disease affecting 12 million people worldwide (17).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, a key strength of GIP and giptools is the general applicability to different eukaryotic species. We already successfully applied GIP on the analysis of Leishmania genomes (14–16). In this study, we validate the use of GIP and giptools using WGS data from published datasets of the three major human pathogens Leishmania infantum , Plasmodium vivax and Candida albicans and as well as three human cancer cell lines.…”
Section: Main Textmentioning
confidence: 99%
“…However, these reactions generally either amplify genus- or subgenus-specific conserved regions and do not allow species identification. Recent development of a barcoding-like approach based on high-throughput sequencing of kDNA amplicons and minicircle sequence comparisons may allow in the future a reliable identification of Leishmania species in kDNA qPCR-positive specimens [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%